Implementation of Coaching and Mentoring in Clinical Academic Supervision to Improve Teaching Quality in Secondary Schools - Harmita Harmita; Siti Sainah; Sri Wulan Wahyuningsih; Mohamad Muspawi; Eva Iryani; Denny Denmar (Journal of Educational Sciences, 2026)
Academic supervision plays an important role in improving the quality of classroom learning; however, it is often implemented as an administrative activity rather than as a developmental process. This study aims to investigate the implementation of coaching and mentoring within academic supervision to enhance teaching quality. The study employed a qualitative descriptive approach using the clinical supervision framework proposed by Cogan and Goldhammer. Six key informants participated in this study, consisting of two school principals as supervisors and four teachers who had experienced the supervision process. Data were collected through in-depth interviews, classroom observations, and documentation, and were analyzed using the interactive model of data analysis. The findings indicate that coaching and mentoring are systematically integrated across five stages of clinical supervision: pre-observation, classroom observation, analysis and interpretation, reflective feedback, and follow-up mentoring. The results show that collaborative planning, objective observation, reflective dialogue, and continuous mentoring support teachers in improving instructional practices. It can be concluded that the integration of coaching and mentoring within academic supervision creates a supportive professional learning environment that contributes to sustainable improvement in teaching quality and classroom learning.